KAPABILITAS KARYAWAN SEBAGAI FAKTOR PEMBENTUK LEARNING AND GROWTH ORGANIZATION - Dwita Darmawati; Sri Lestari; Utami Puji Lestari (Faculty of Economics and Business Universitas Jenderal Soedirman, 2008)
The aims of this research are to analize the degree of employee statisfication and employee retention at Purwokerto Islamic Hotel. Descriptive methode and single case holistic explorative used in this research. Qualitative and quantitative data were used in this reseach, and 48 employesss of Purwokerto Islamic Hospital participated in this research. Data collected by questioner, interview, and literature study. The result indicated that the the employee shows statisfied with their jobs. The employee retention in 5 years latest around 1-4 percent and showing decreasing trend. The implication of this research are the following: 1) Purwokerto Islamic Hospital has to retain its human resources policy, and 2) Purwokerto Islamic Hospital has to formulate regulation that tied employee to stay in Purwokerto Islamic Hospital so the new employees are no too easy to resign from Purwokerto Islamic Hospital.